2003
DOI: 10.1111/1467-9353.00054
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Ultrasound Technology to Improve Livestock Marketing Decisions

Abstract: This study estimates the value of using ultrasound technology to improve cattle marketing decisions by optimally choosing a particular marketing method. For the particular group of cattle analyzed, results indicate that using ultrasound information to selectively market cattle could have increased revenue by $25.53/head, $4.98/head, or $32.90/head, compared with simply marketing all animals on a live weight, dressed weight, or grid basis, respectively. Even if producers incorporate such information as placemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 13 publications
1
15
1
Order By: Relevance
“…(1996) showed that ultrasound measures, taken on cattle prior to feedlot feeding, combined with performance data collected during the finishing phase, could effectively predict LMA, SFD and IMF percentage at any point during the finishing phase. The ability to predict the optimum slaughter date of a particular animal is an attractive use of ultrasound technology (Lusk et al ., 2003). The RTU can be used to develop models to predict the number of days necessary to reach a target carcass composition under a defined feeding regime (Hassen et al ., 1999a), or to develop a feeding regime that maximizes the production of carcasses with a higher-yield or higher-quality grade (Basarab et al ., 1999).…”
Section: Predicting Optimum Slaughter Datementioning
confidence: 99%
See 4 more Smart Citations
“…(1996) showed that ultrasound measures, taken on cattle prior to feedlot feeding, combined with performance data collected during the finishing phase, could effectively predict LMA, SFD and IMF percentage at any point during the finishing phase. The ability to predict the optimum slaughter date of a particular animal is an attractive use of ultrasound technology (Lusk et al ., 2003). The RTU can be used to develop models to predict the number of days necessary to reach a target carcass composition under a defined feeding regime (Hassen et al ., 1999a), or to develop a feeding regime that maximizes the production of carcasses with a higher-yield or higher-quality grade (Basarab et al ., 1999).…”
Section: Predicting Optimum Slaughter Datementioning
confidence: 99%
“…Ultrasound provides information about the carcass of each animal individually, and if the data are collected when animals start on feed, it can also provide information that can be used to sort animals into adequate feeding regimes (Lusk et al ., 2003). Therefore, RTU contributes to reducing the problem of overfeeding, improves the efficiency of the production system and increases the income of the meat producers (Lusk et al ., 2003;Pyatt et al ., 2005).…”
Section: Sorting Animals Prior To Feedlot Feedingmentioning
confidence: 99%
See 3 more Smart Citations